Examining Engagement and Interaction of Children With Disabilities in Inclusive Kindergartens in China. Issue 2 (April 2016) - Hu, Bi Ying; Lim, Chih-Ing; Boyd, Brian
Abstract : Quality engagement in early childhood programs is critical to the development and learning of young children, particularly those with disabilities. The purpose of this study was to examine the quality of engagement and interaction of children with disabilities in inclusive kindergartens in China. Specifically, the study aimed to examine the engagement and interaction levels children with disabilities had across 5 types of activities (i.e., group teaching, mealtime, self-care, play, outdoor activities) and subject matter for whole-group lessons (i.e., music, storytelling, art, language art, math and science, and general knowledge or life skills). Participants in this study included 13 children with varying disabilities from 5 inclusive kindergarten programs in Beijing. A total of 127 observation sessions were collected across the 5 activities, with a mean of 104.27 min of observation per child. The sessions were then analyzed using the Individual Child Engagement Record (Y., Kishida; C. R., Kemp, & M., Carter, 2008 ). Results indicate that there were differences in the level of engagement and interaction for children with disabilities across activities and subject areas. Implications for practice and future research are discussed.